Mobilizing young people as climate-smart agriculture infomediaries: What do we know? - Manalo, Jaime A.; Berto JC; Balmeo KP; Saludez, Friedierick M.; Villaflor, Jennifer D.; Pagdanganan, Argie M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
While efforts to adapt to the impacts of climate change have generally increased, the impression is that there is a negligible effort to include the vulnerable areas on the agenda. This paper seeks to fill in the gap by presenting an agricultural extension mechanism to tap high school students as information providers of climate-smart rice agriculture information in their rice-farming communities. This paper looks at the characteristics of the high school students who served as infomediaries as well as their information sources and perceptions on climate change; the best teaching media that can be used; and the infomediation pathways that can be drawn from this initiative. Two survey rounds, 2014 (n=) and 2015(n=), were used as data sources. Focus group discussions and interviews were also conducted. Chi-square tests were also employed. Data show that females are more likely to be infomediaries than males. Schools serve as the primary sources of information on climate change, and students generally equate climate change to extreme weather events such as drought. Various teaching media explored seem to be useful in various development contexts. Teachers are seen as the champions of this initiative. Hence, this initiative rests heavily on the extent of capacity enhancement that can be extended to the teachers so they are in a better position to train their students in the future.